A morse-code recognition system with LMS and matching algorithms for persons with disabilities - Shih, Ching-Hsiang; Luo, Ching-Hsing (International journal of medical informatics (Shannon, Ireland), 1997)
Single-switch communication is an effective auxiliary method for persons with disabilities. However, it is not easy to recognize the Morse codes typed by them. In our earlier proposed Morse code auto-recognition method, using the Least-Mean-Square (LMS) adaptive algorithm, it was demonstrated that the system could successfully recognize the Morse-coded messages at unstable typing speeds. However, the speed variation had to be limited to a range between 0.67 and two times the present speed. In the case of beginners or those with heavy disabilities, this rule can not always be complied with, producing a low recognition rate of 20%. To address this limitation, this paper offers an advanced recognition method which combines the Least-Mean-Square algorithm with a character-by-character matching technique. The recognition rate for this method from simulated and real data from various sources is as high as 75% or more on average. This practical application of the single-switch method means a step forward toward alternative communication for disabled persons.